Criteria for the selection and the principle of structural diversity in stream cipher cascading - Glavchev, Maksym; Panchenko, Volodymyr; Bulykin, Yehor (Одеський національний технологічний університет, 2025)
The study substantiates the critical importance of applying the principle of structural diversity in the selection of stream ciphers for cascaded cryptographic systems. It examines the risks associated with homogeneous cascading, where a single vulnerability within one class of algorithms may result in the complete compromise of the entire system. The paper formulates key criteria for selecting cryptographic primitives, emphasizing their mathematical foundations, resilience against diverse categories of cryptanalytic attacks, and computational efficiency. As a practical illustration, the effectiveness of a heterogeneous cipher pair – AES-CTR and ChaCha20 – is demonstrated and analyzed.
Keywords: criteria for the selection; principle of structural diversity; cascading; stream cipher; cryptographic systems; compromise